Digital Journalism and Citizen Engagement in Nigeria - Tari Johnson; Mmesomachukwu Chukwuemeka Iloh; Margaret Solo-Anaeto; Carol Dixon Odoyi (Matondang Journal, 2025)
This paper focuses on the place of digital journalism and citizen engagement in Nigeria. Digital journalism has maintained its relevance through the advent of digital media which has fostered citizen engagement. Digital media such as Facebook, Twitter, and so on has allowed various news organizations and individuals to own a page on their platforms which has made the citizens of Nigeria aware of the news going on in their locality via electronic means and allowed them to give any form of rebuttal to any policy or activities of the government that are not welcomed by them. The democratic participation and the uses and gratifications theories of the media were used to guide this paper. It was acknowledges that digital media which serves as a tool for digital journalism and citizen engagement possesses the potential to bring about online citizen engagement among Nigeria’s population through offering them a platform for acquiring information necessary for citizen participation; for engaging in political discussions/debates in an atmosphere of enhanced freedom of speech; for direct conversations with elected representatives; for pushing for change; and for achieving group mobilization. The paper, however, argues that before digital media could effectively perform these roles as a tool for digital journalism and citizen engagement, certain factors must first be addressed and these include the extent of the youth’s interest in politics, the conduciveness (or helpfulness) of the political environment and the responsiveness of the government of the day to the citizen engagement cause.